Traditional and Modern Medicine in the Context of Globalization - World Bank (Washington, DC, 2012)
During the workshop organized by traditional healers at the XIIIth International HIV/AIDS Conference in Durban, South Africa in July 2000, the issue of the legal recognition and the legal status of this ancestral form of healing was once again discussed. The healers underlined the important role that they play in the preservation and rehabilitation of their fellow citizens' health, with at least 75 percent of the African population using their services.